Effectiveness of Structured Lactation Education on Increasing Breast Milk Production in Postpartum Mothers - Mariati, Nelly; Ulfa, Siti Maria (Oshada, 2025)
Breast milk (ASI) is the best nutrition for newborns because it contains complete nutrients and immunological factors that cannot be replaced by formula. Although the WHO recommends exclusive breastfeeding for the first six months of life, the coverage of this practice in Indonesia remains low due to various barriers, particularly the perception of breast milk insufficiency, inappropriate breastfeeding techniques, and minimal support from families and health workers. Structured lactation education presents a comprehensive strategy to improve breastfeeding success through a systematic approach, encompassing physiological, psychological, and social aspects. This approach not only provides technical knowledge such as breast care and baby attachment techniques, but also strengthens maternal confidence through repeated counseling and emotional support. Research shows that structured education can increase the oxytocin reflex, improve practical skills, and reduce postpartum maternal anxiety. A qualitative method based on a literature review was used to examine empirical evidence regarding the effectiveness of this intervention from various international and national publications. The study results indicate that structured lactation education has a positive impact on increasing breast milk production, exclusive breastfeeding success, and the quality of life of mothers and babies. Its implementation also has policy implications, including strengthening the health care system, regulations supporting lactation, and the provision of supporting facilities. Thus, structured lactation education can be considered a long-term health investment that contributes to public health development and the achievement of global goals.